2022
DOI: 10.3389/fpubh.2022.896061
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Hybrid Multi-Criterion Decision-Making Model for Evaluation and Improvement of Nurses' Job Satisfaction

Abstract: BackgroundThe global shortage and turnover of nurses is a current challenge. Past studies have shown that nurse job satisfaction may ameliorate nurse shortage. Although there are many studies on the criteria influencing nurses' job satisfaction, few have examined the causal relationships and weight of each criterion from a systematic perspective.ObjectiveIdentify the key criteria and causal relationships that affect nurses' job satisfaction, and help nurse leaders identify high-weight, high-impact dimensions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The DEMATEL method is a system structure analysis that analyzes the complex social network structure of problems in the real world using the practical experience of a group of experts ( 22 , 23 ). This method can analyze the interaction between subsystems in a system and visualize it using graph theory, to construct an influence network diagram ( 24–26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The DEMATEL method is a system structure analysis that analyzes the complex social network structure of problems in the real world using the practical experience of a group of experts ( 22 , 23 ). This method can analyze the interaction between subsystems in a system and visualize it using graph theory, to construct an influence network diagram ( 24–26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Importance-Performance Analysis (IPA) method is used to evaluate the relative importance of various factors in a system or process and to identify areas for improvement. Since then, it has been widely used in the fields of nurses job satisfaction ( 27 , 28 ), shared decision-making ( 29 ), and university-teacher development ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…The "pay" survey scores indicate that employees are satisfied with what they are getting fair pay but less satisfied with the chances for salary increases in future, indicating employees are happy with their current financial situation but may have future concerns about future pay, which may impact their employment longevity and career choices. According to research (Liu, et al, 2022) that assessed nurses' job satisfaction in China found that pay and benefits were the most important factors in nurses' job satisfaction. For many expatriates, financial incentives are a key motivator for working abroad due to higher salary packages compared to their home country.…”
Section: Job Satisfactionmentioning
confidence: 99%